Tingkat Penerapan Manajemen Mutu pada Usaha IKM Chide Wrought Iron Design - Dewi Sinta Kusumawardani; Ma'mun Sarma; Aris Munandar (Institut Pertanian Bogor, 2012)
Small and Medium Enterprises (SMEs) is one of a growing economic activity and income real contribution to society. There are variety of products, qualities level and quantities they made. SMEs with good quality product and affordable price is choosen by society. This research is aimed to identify the level of quality managemet applications in SMEs. Data collection techniques with census method, using the tools of the questionnaire is enclosed with a Likert scale (1-5) in the form of verbal categories strongly agree-strongly disagree. Data were analyzed descriptively to look at consumer perceptions of the statements in the questionnaire with the Technique Criteria Range. To find out the company's performance using the BSC. The research showed that the quality management has been perceived to be well implemented by company owner, employee, consumer and distributor. The result and analysis for ChiDe Wrought Iron Design using BSC method show: (1) financial aspect is healthy showed by rentability, liquidity and solvability ratio above 100%; (2) customer perspective showed from enterprise capability to maintain customer 8 out of 13 (61,5%) has been loyal for 3 years; (3) internal business process is quite good from stand poin of innovation capability and operation. After sale service were not carried out carefully; (4) organization learn and growth is stated by employees satisfaction is quite good (96%). As small as ChiDe Wrought Iron Design SMEs ISO 9000 seems not important to be implemented, basic reason for the thought are the consumer doesn’t require ISO 9000 certifications as guarantee for good quality. The most important thing and need to be developed by company is the commitment to quality product (realibility of the product), efficiency, effectivity, productivity and continuous improvement of production process